Sensitivity Cost-Benefit Analysis to Support Knowledge Capture of Industrial Interests - Paci, A. M.; Chiacchio, M. S. (Cranfield University Press, 2009)
In strategic industrial fields, emerging technologies are evolving into strategic enabling technologies for next generation products and services (IPS2). To this end a new approach to market knowledge capture needs early impact assessment of costs and value benefits considering the broad variety of factors of sustainability in medium-long term. This paper presents the framework for new IPS2 and a new methodology for Sensitivity Cost-Benefit Analysis (SCBA). SCBA aims to evaluate new IPS2, based on RTD potential, applying the AHP (Analytic Hierarchy Process) technique. The evaluation results support stakeholders in market knowledge capture about new IPS2 based on new enabling technologies.
Organised by: Cranfield University
Keywords: Cost-Benefit; Impact assessment; Production paradigms